2013
DOI: 10.1007/s40273-013-0067-0
|View full text |Cite
|
Sign up to set email alerts
|

A Choice That Matters?

Abstract: FFE, FRE and BFE lead to comparable HE outcomes. BRE tends to overestimate uncertainty. Based on this study, we recommend FRE as the preferred method of meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Compared to a few large trials, the effect of having more but smaller trials and trials with differences in trial sizes, on the performance of different methods of meta-analysis is small. [ 11 ] We therefore feel our study results are generalizable to many other situations where parameters for a HE model are obtained through MTC.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Compared to a few large trials, the effect of having more but smaller trials and trials with differences in trial sizes, on the performance of different methods of meta-analysis is small. [ 11 ] We therefore feel our study results are generalizable to many other situations where parameters for a HE model are obtained through MTC.…”
Section: Discussionmentioning
confidence: 57%
“…The simulation study, as well as the disease and HE model structure as discussed in section 2.2, is identical to that used in the earlier publication. [ 11 ] The simulation consists of five steps ( Fig 1 ). In step 1: Create reference population , we simulated a superpopulation [ 12 ] containing 50,000 patients.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the treatment effect observed in an outcomes study may differ from the one observed in an RCT. Although this difference in treatment effect has been modeled in our article with an additional input parameter, the most common approach would be to perform a patient-level simulation analysis [10,26]. Thus, accounting explicitly for heterogeneity would change the methods considered in our article.…”
Section: Discussionmentioning
confidence: 99%
“…Patients can be in four different health states: moderate, severe, very severe, and dead. The disease progression is described by a Markov model similar to the one introduced by Vemer et al [10]. The model is set up for 36 cycles of 1 month.…”
Section: Model and Interventionsmentioning
confidence: 99%